Defining Supply Chain Visibility for Industrial Construction Projects - Dharmapalan, Vineeth; O’Brien, William J.; Morrice, Douglas J. (Frontiers in Built Environment, 2021)
Good Supply Chain Visibility (SCV) is vital for on-time delivery and installation of materials on industrial construction projects. SCV is possible via the exchange of information about materials in the supply chain. Prior academic research has highlighted the importance of SCV. However, the literature lacks the detailed definition of visibility that can be easily applied to projects. This research reviewed prior studies on SCV and adopted an appropriate definition that supports relevant decision-making on industrial construction projects. From this definition, the research objective is to develop detailed operational definitions of information needed to support supply chain decisions on industrial construction projects. The study employed mixed methods that consisted of interviews, review of mini-cases of industrial projects, procurement and material tracking tool assessment, and group discussions in structured workshops with a panel of subject matter experts. The research developed 79 detailed information needs and associated definitions that support ten key supply chain decision areas across detailed design, procurement, and construction phases of industrial construction projects. These definitions were evaluated by multiple means including an external team and a case study of an industrial construction project. The definitions developed by this research will enable both researchers and practitioners to invest in better measurements of visibility and support development of new tools and techniques.